Characterization of electrodes chemically modified with Mn(III) porphyrin/polypyrrole films as catalytic surfaces for an azo dye - Barros, Valeria P.; Zanoni, Maria Valnice Boldrin [UNESP]; Assis, Marilda das D. (Soc Porphyrins & Phthalocyanines, 2006)
In this study we describe the electrochemical behavior of 5,10,15,20-tetrakis(2'-aminophenylporphyrin)manganese(III) chloride supported on a glassy carbon electrode, as well as the electrochemical preparation and characterization of thin films based on pyrrole-3-carboxylic acid. The electrocatalytic action of the electrode modified with the Mn(III) porphyrin toward an azo dye was tested, and the characteristic strong interaction between the incorporated metalloporphyrin and RR120 dye was verified. Copyright (c) 2006 Society of Porphyrins & Phthalocyanines.
Keywords: manganese porphyrin; azo dye; electrodes modified; electrodeposition; RR120 dye